Spatial and Temporal Abundance of Interacting Populations of White Clover and Grass Species as Assessed by Image Analyses. (8th May 2015) - Bakken, Anne Kjersti; Bonesmo, Helge; Pedersen, Bård
Abstract : The dataset comprises detailed mappings of two communities of interacting populations of white clover ( Trifolium repens L.) and grass species under differing experimental treatments over 4-5 years. Information from digital photographs acquired two times per season has been processed into gridded data and documents the temporal and spatial dynamics of the species that followed from a wide range of spatial configurations that arose during the study period. The data contribute a unique basis for validation and further development of previously published models for the dynamics and population oscillations in grass-white clover swards. They will be well suited for estimating parameters in spatially explicit versions of these models, like neighborhood based models that incorporate both the dispersal and the local nature of plant-plant interactions.